2009
DOI: 10.1161/circulationaha.108.832782
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory T Cells Ameliorate Angiotensin II–Induced Cardiac Damage

Abstract: Background-Hypertensive target organ damage, especially cardiac hypertrophy with heart failure and arrhythmia, is a major source of morbidity and mortality. Angiotensin II, a major mediator of hypertension and cardiac damage, has proinflammatory properties. Inflammation and activation of the immune system play a pivotal role in pathogenesis of hypertensive target organ damage. However, the role of immunosuppressive CD4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
211
3
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(228 citation statements)
references
References 51 publications
11
211
3
3
Order By: Relevance
“…In contrast, proteins involved in actin-filament organization, lymphocyte activation (including T-cell activation), and cell projection organization (including neuron projection development and axonogenesis) were enriched in hypertrophic but not acutely stressed hearts (Table I). This finding is consistent with T-cell infiltration and sympathetic nerve generation being increased in hypertrophic hearts (38,39). Our analyses showed that different cellular pathways were activated in cardiac myocytes in response to acute or chronic pressure overload.…”
Section: Quantification Of Dynamic Phosphoproteomic Profiles Respondisupporting
confidence: 91%
“…In contrast, proteins involved in actin-filament organization, lymphocyte activation (including T-cell activation), and cell projection organization (including neuron projection development and axonogenesis) were enriched in hypertrophic but not acutely stressed hearts (Table I). This finding is consistent with T-cell infiltration and sympathetic nerve generation being increased in hypertrophic hearts (38,39). Our analyses showed that different cellular pathways were activated in cardiac myocytes in response to acute or chronic pressure overload.…”
Section: Quantification Of Dynamic Phosphoproteomic Profiles Respondisupporting
confidence: 91%
“…8,9,15 Both the innate and the adaptive immune responses have been implicated in cardiovascular disease, particularly in hypertensive renal pathology 16 and, more recently, in vascular and heart disease. 12,[17][18][19] Indeed, it was previously showed that the innate immune system is involved in Ang II and DOCA/salt-induced hypertension and vascular injury and in aldosterone-induced vascular damage in a blood pressure-independent fashion. [11][12][13] Other investigators have as well more recently confirmed a Figure 1.…”
Section: Discussionmentioning
confidence: 99%
“…13) Matsumoto, et al also reported that transfer of Tregs attenuated myocardial infarction-induced ventricular remodelling in mice. 14) These fi ndings suggest that peripheral circulating Tregs might be involved in the pathogenesis of left ventricular dysfunction during development of heart failure.…”
Section: Cd4mentioning
confidence: 97%